One Map Policy: Digital Administration Methods as an Effort to Solve Land Overlaps in Indonesia - PALENGKAHU, Muhammad Rahjay (Journal of Social Sciences and Cultural Study, 2023)
Only now has Indonesia's land use problem been partially found to be a bright spot. Moreover, the government created the map that gave rise to this issue. Therefore, holding the One Map Policy in government policies is necessary to realize good land governance. This research aims to determine how effective the One Map Policy is in solving land problems and realizing good spatial governance to provide welfare to the people. This research is written using normative juridical methods, using literature studies that examine a problem from a legal point of view and look for data in reading materials. So, the One Map Policy is one of the alternatives and essential policies to resolve overlapping land uses in the community. Indonesia is a country that has a rich nature and can used by humans. It is the same as what has been loaded in the 1945 Constitution in Article 33, paragraph 3, which explains that earth, water, and wealth contain nature inside it, controlled by the state and used for as big possible prosperity of the people.